Epulis granulomatosa in a pediatric patient - Valvano, Beatriz Menegon; Rodrigues, Bruno Teixeira Gonçalves; Romañach, Mário José; de-Andrade, Bruno Augusto Benevenuto; Israel, Mônica Simões (Journal of Oral Diagnosis, 2022)
Introduction: Epulis granulomatosa is a post-surgical lesion emanating from an extraction socket. It can be misdiagnosed with other lesions that have similar clinical appearances, such as foreign body and pyogenic granuloma. Excisional biopsy stands as its gold-standard treatment followed by histopathological analysis in order to establish the diagnosis Objective: The aim of the present study was to report an illustrative case of epulis granulomatosa occurring after tooth extraction in a pediatric patient. Case Report: A 5-year-old boy claiming about an exophytic lesion in the alveolar mucosa at the anterior region of the mandible was noticed after deciduous lower right central incisor tooth extraction. Diagnosis of granulomatous epulis was confirmed after histopathological examination performed through excisional biopsy. Conclusion: The patient’s recovery was uneventful, and no signs of local recurrence could be observed up to this date.